Implications of Differential Peroxyl Radical-Induced Inactivation of Glucose 6-Phosphate Dehydrogenase and 6-Phosphogluconate Dehydrogenase for the Pentose Phosphate Pathway - Arenas-Salinas, F (Nature Research, 2022)
Escherichia coli glucose-6-phosphate dehydrogenase (G6PDH) and 6-phosphogluconate dehydrogenase (6PGDH) are key enzymes of the pentose phosphate pathway, responsible for the NADPH production in cells. We investigated modification of both enzymes mediated by peroxyl radicals (ROO·) to determine their respective susceptibilities to and mechanisms of oxidation. G6PDH and 6PGDH were incubated with AAPH (2,2′-azobis(2-methylpropionamidine)dihydrochloride), which was employed as ROO· source. The enzymatic activities of both enzymes were determined by NADPH release, with oxidative modifications examined by electrophoresis and liquid chromatography (LC) with fluorescence and mass (MS) detection. The activity of G6PDH decreased up to 62.0 ± 15.0% after 180 min incubation with 100 mM AAPH, whilst almost total inactivation of 6PGDH was determined under the same conditions. Although both proteins contain abundant Tyr (particularly 6PGDH), these residues were minimally affected by ROO·, with Trp and Met being major targets. LC–MS and in silico analysis showed that the modification sites of G6PDH are distant to the active site, consistent with a dispersed distribution of modifications, and inactivation resulting from oxidation of multiple Trp and Met residues. In contrast, the sites of oxidation detected on 6PGDH are located close to its catalytic site indicating a more localized oxidation, and a consequent high susceptibility to ROO·-mediated inactivation. © 2022, The Author(s).